Diagnosis and Management of Small-Scale and Data-Limited Fisheries - Mohamed Samy-Kamal; Célia M. Teixeira (Fishes, 2023)
Historically, small-scale fisheries (SSFs) have largely been overlooked by fisheries scientists and management authorities at national and international levels [...]